Sintesis Nanopartikel Perak Menggunakan Ekstrak Daun Bidara Ziziphus Spina-Christi Dan Uji Aktivitas Antibakteri Terhadap Bakteri Staphylococcus Aureus - Cut Dian Mala Luthfia; Dikki Miswanda; Haris Munandar Nasution; Minda Sari Lubis (OBAT: Jurnal Riset Ilmu Farmasi dan Kesehatan, 2024)
Nanotechnology is currently growing rapidly due to its broad application in science and technology. Nanotechnology itself is a science based on nanoparticles, so a more environmentally friendly method is being developed, namely the "green synthesis" method using plant extracts as a bioreductor. Silver nanoparticles have been synthesized using extracts of bidara leaf as a reducing agent. The objective of this research was was to determine the synthesis of silver nanoparticles using bioreductors and their application as antibacterial agents using bidara leaf extract against Staphylococcus aureus bacteria. This research used the green synthesis method to produce silver nanoparticles. The bidara leaf extract used was divided into several concentrations, namely 1 mM, 2 mM, 3 mM and 4 mM. To characterize silver nanoparticles, UV-Vis and PSA spectrophotometers were used. Furthermore, the Kirby-Bauer method was used to test the antibacterial properties of silver nanoparticles against Staphylococcus aureus bacteria. The results of research that has been done show that the formation of silver nanoparticles is characterized by the emergence of maximum absorbance peaks in the wavelength range of 400-450 nm, while the PSA results at concentrations of 3 and 4µm showed nanoparticle sizes of 185 nm. Silver nanoparticles of bidara leaf extract with various concentrations of 1 mM, 2 mM, 3 mM and 4 mM have antibacterial activity that can inhibit the growth of Staphylococcus aureus bacteria with an average inhibition zone diameter of 13.0617 mm, 11.7333 mm, 9.05 mm and 13.19 mm. This shows that silver nanoparticles with bidara leaf extract have antibacterial properties.